Electromyographic Pattern during Gait Initiation Differentiates Yoga Practitioners among Physically Active Older Subjects - Lelard, Thierry; Doutrellot, Pierre-Louis; Temfemo, Abdou; Ahmaidi, Said (Frontiers in Human Neuroscience, 2017)
During gait initiation, postural adjustments are needed to deal with balance and movement. With ageing, gait initiation changes and reflects functional degradation of frailty individuals. However, physical activities have demonstrated beneficial effects of daily motor tasks. The aim of our study was to compare center of pressure (COP) displacement and ankle muscle co-activation during gait initiation in two physically active groups : a group of walkers (n=12; mean age  SD 71.53.8y) and a yoga group (n=11; 72.63.2y). COP trajectory and electromyography of leg muscles were recorded simultaneously during five successive trials of gait initiation. Our main finding was that yoga practitioners had slower COP displacements (p<0.01) and lower leg muscles % of coactivation (p<0.01) in comparison with walkers. These parameters which characterized gait initiation control were correlated (r=0.76; p<0.01). Our results emphasize that lengthy ankle muscle co-activation and COP path in gait initiation differenciate yoga practitionners among physically active subjects.